2018
DOI: 10.1002/pip.2984
|View full text |Cite
|
Sign up to set email alerts
|

NeoGrowth silicon: A new high purity, low‐oxygen crystal growth technique for photovoltaic substrates

Abstract: SolarWorld has developed a new entrant in the field of crystal growth for silicon photovoltaic substrates. The NeoGrowth technique is a contactless bulk crystal growth method for producing single crystal ingots. NeoGrowth material can be produced at a throughput on par with G5 multicrystalline silicon, but with p-type as-grown minority carrier lifetimes exceeding 600 microseconds for a 1.5-ohm cm resistivity. The silicon has low oxygen, and light-induced degradation is measured at 0.5% to 0.7% in passivated em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Only material from the non-seed part of the ingot is used in this investigation. The process, called NeoGrowth, 37 has no containment crucible and thus no foreign contact during crystal growth, providing capability for very high purity ingots. As in most silicon crystal growth, iron is the chief quality-limiting impurity despite the availability of contact-diffusion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only material from the non-seed part of the ingot is used in this investigation. The process, called NeoGrowth, 37 has no containment crucible and thus no foreign contact during crystal growth, providing capability for very high purity ingots. As in most silicon crystal growth, iron is the chief quality-limiting impurity despite the availability of contact-diffusion.…”
Section: Methodsmentioning
confidence: 99%
“…No Fe was deliberately introduced to the material, but in typical directionally solidified silicon, some degree of Fe contamination is practically impossible to avoid. 37,42 Graphite and insulation parts can, for example, be significant sources of iron, circulated by evaporation. In the wafers used for this study, a dramatic increase in carrier lifetime was observed after phosphorous diffusion 39 suggesting the presence of a mobile metal contaminant as the lifetime limiting source.…”
Section: A Minority Carrier Lifetime Measurementsmentioning
confidence: 99%
“…A limitation, however, exists for the global temperature field because a constant emissivity is employed outside the probe region. This effect can be analysed by assuming εT 4 = const from which the following estimation is derived:…”
Section: Description Of Experimentsmentioning
confidence: 99%
“…In this case, dislocation generation is believed to be caused primarily by high thermal stresses. By adjusting the temperature gradients, the stress level and the final dislocation density in the crystal can be lowered [4].…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen in silicon usually originates from the silica crucibles which contain the melt. Whilst low oxygen concentrations can be achieved by modifying the Czochralski process with magnetic fields (~3 × 10 17 cm −3 ) or novel processes such as NeoGrowth (~4 × 10 17 cm −3 ), the production of such crystals is relatively expensive or immature. Float‐zone silicon (FZ‐Si) has lower oxygen concentrations than Cz‐Si or mc‐Si (usually <5 × 10 15 cm −3 ) but comes with other lifetime stability issues probably due to complexes associated with intrinsic point defects and is also much more expensive.…”
Section: Introductionmentioning
confidence: 99%